Perancangan Aplikasi To-do-list "MyList" - Firdaus, Muhamad Julian; Manikam, Ratna Mutu (FORMAT, 2025)
Effective task management is crucial in today’s fast-paced world, where productivity and organization are essential. Addressing this need, MyList is designed as a mobile-based to-do list application that simplifies and optimizes task organization for users. The application features task creation, editing, deletion, categorization, prioritization, reminders, and progress tracking through visual statistics, fostering motivation and efficiency. Developed using the Waterfall methodology, the design process includes requirement analysis, system design, and user interface mockups. The application employs Android Studio, Java programming, and MySQL database management to ensure compatibility, reliability, and efficiency across Android platforms. MyList is lightweight, accessible, and tailored to diverse audiences, including students and professionals seeking better time management. Its user-friendly interface prioritizes simplicity and functionality, making it a practical solution for daily task management. While this study focuses on the design phase, the proposed application demonstrates significant potential for implementation and real-world testing. The anticipated outcomes include improved productivity, enhanced time management, and seamless task organization for users. This research serves as a foundation for developing innovative and user-centric task management solutions, encouraging future advancements and practical applications in this domain.